What constitutes a 'successful' recovery? Patient perceptions of the recovery process after a traumatic injury. Issue 1 (23rd February 2020) - Rosenberg, Graeme; Zion, Sean R; Shearer, Emily; Bereknyei Merrell, Sylvia; Abadilla, Natasha; Spain, David A; Crum, Alia J; Weiser, Thomas G
Abstract : Background: As the number of patients surviving traumatic injuries has grown, understanding the factors that shape the recovery process has become increasingly important. However, the psychosocial factors affecting recovery from trauma have received limited attention. We conducted an exploratory qualitative study to better understand how patients view recovery after traumatic injury. Methods: This qualitative, descriptive study was conducted at a Level One university trauma center. Participants 1–3 years postinjury were purposefully sampled to include common blunt-force mechanisms of injuries and a range of ages, socioeconomic backgrounds and injury severities. Semi-structured interviews explored participants' perceptions of self and the recovery process after traumatic injury. Interviews were transcribed verbatim; the data were inductively coded and thematically analyzed. Results: We conducted 15 interviews, 13 of which were with male participants (87%); average hospital length of stay was 8.9 days and mean injury severity score was 18.3. An essential aspect of the patient experience centered around the recovery of both the body and the 'self', a composite of one's roles, values, identities and beliefs. The process of regaining a sound sense of self was essential to achieving favorable subjective outcomes. Participants expressed varying levels of engagement in their recovery process, with those on the high end of the engagement spectrum tending to speak more positively about their outcomes. Participants described their own subjective interpretations of their recovery as most important, which was primarily influenced by their engagement in the recovery process and ability to recover their sense of self. Discussion: Patients who are able to maintain or regain a cohesive sense of self after injury and who are highly engaged in the recovery process have more positive assessments of their outcomes. Our findings offer a novel framework for healthcare providers and researchers to use as they approach the issue of recovery after injury with patients. Level of evidence: III—descriptive, exploratory study.